Chemically enhanced water-alternating-gas injection for improved CO2 sweep efficiency and geological sequestration in CO2-EOR: Insights from physical experiments and molecular simulation - Pengwei Fang; Zhengming Yang; Qun Zhang; Hongwei Yu; Fei Feng; Yidi Wan; Jiangfei Wei; Yuhao Mei; Meiwen Cao (Results in Engineering)
Addressing gas channeling, limited sweep efficiency, and restricted CO2-oil miscibility in heterogeneous reservoirs during CO2-enhanced oil recovery (CO2-EOR) remains a critical challenge. Herein, a novel pressure-regulated, hydrophilic CO₂-responsive hydrogel-to-foam transition system is used to enhance oil recovery and synergistically facilitate geological CO₂ sequestration. By molecular engineering of a quaternary ammonium surfactant (HXA-1) with unsaturated alkyl chains and hydrophilic moieties, the system achieves ultralow oil-water interfacial tension and adaptive micellar structures, enabling in-situ gel-to-foam phase transition under CO2 pressure. Core flooding experiments demonstrate that the Chemical-Assisted Water-Alternating-Gas (CWAG) technique forms a stable piston-like displacement front, boosting oil recovery by 16 % compared to conventional WAG while achieving 91.2 % plugging efficiency. In-situ visualization and molecular dynamics simulations reveal that the hydrophilic surfactant mitigates water-phase shielding and hydrophobic interactions, promoting CO2/oil miscibility and emulsification. Furthermore, the system exhibits dual functionality: under reservoir conditions, a 0.35 wt% HXA-1 solution absorbs twice as much CO2 as WAG, significantly enhancing sequestration, while the dynamic phase transition enables deep conformance control in heterogeneous reservoirs. This work pioneers a multifunctional CO2-responsive material platform, offering transformative solutions for sustainable fossil fuel extraction and carbon capture, utilization, and storage (CCUS) technologies.